Organización contable en la Empresa PLC SKIN Cia.Ltda., de la ciudad de Loja, periodo del 01 de abril al 30 de junio del 2023. - Quizhpe Cabrera, Dayana Elizabeth (2024)
The Curricular Integration Work entitled Accounting Organization in the Company PLC SKIN CIA.LTDA., from the city of Loja, period from 01 April to 30 June 2023, was developed with the aim of carrying out an appropriate accounting process and providing valuable information about the financial situation of the company. The methodology of the work was based on the mixed approach of descriptive exploratory type and non-correlational design, the scientific method and research techniques were used. In order to the objectives set out, an accounting plan and manual adapted to the needs of the company was developed in order to properly record and organize its economic activities. A physical verification of the initial inventory confirmed the existence of assets for a total of $156,578,35, liabilities for $598,60 and equity for $155,979,75, thereby establishing the initial statement. All source documentation was sorted and classified by drawing up the transaction memorandum for the ordered and chronological recording of transactions in the diary, using the multi-account system. The main book, balance sheet, working paper, financial statements and explanatory notes were then prepared. At the end of the accounting process applied to the company "PLC SKIN CIA.LTDA.", the information reflected in the financial statements has an utility of $4,922,85, indicating adequate financial management. With this information, the owner of the company will be able to make decisions that favour the economic growth of the business.